Alcohol and Drug Use, Smoking, and Gambling among Psychiatric Outpatients: A 1-Year Prevalence Study. Issue 2 (April 2013) - Nehlin, Christina; Grönbladh, Leif; Fredriksson, Anders; Jansson, Lennart
Background and Aims: Studies of alcohol habits in general psychiatric populations are scarce. The objective was to investigate alcohol and drug use, smoking, and gambling in a clinical sample of psychiatric outpatients. A further aim was to study age and gender differences in the rates of these habits. Methods: Data were collected among psychiatric outpatients with mainly mood (47%) and anxiety (35%) disorders. A questionnaire package was distributed, including AUDIT (Alcohol Use Disorders Identification Test), DUDIT (Drug Use Disorders Identification Test), tobacco items, and gambling items. Two major drinking categories were formed: "Nonhazardous alcohol use" (NH) and "Alcohol use above hazardous levels" (AH). Results: In total, 2160 patients (65% females) responded to the questionnaire package. The AH rate was high among psychiatric outpatients (28.4%), particularly among young females (46.6%). Young female patients also reported a high prevalence of problematic drug use (13.8%). Problematic drug use, daily smoking, and problematic gambling were frequent. The unhealthy habits were linked to AH. Conclusions: Alcohol and drug use, smoking, and gambling are all highly prevalent among psychiatric outpatients. Young females are in particular need of attention. Interventions should be tailored for co-occurring psychiatric disorders and applied within routine psychiatric care.